Design and Development of Mobile Application for Scheduling and Reporting System of Annual Bible Reading Activities of the Seventh Day Adventist Church in West Indonesia Union Miss - Wagiu, Charlene Alicia; Palopak, Yulianus (11th International Scholars Conference, 2017)
The presence of mobile devices makes human work easily as in terms of helping to organize schedules of routine activities. During this time the Seventh Day Adventist Church in Indonesia has an annual Bible reading schedule for all members, but it is still created and distributed in paper form which it is easily damage and even lost. This study aims to develop a mobile application that will be used by the leaders of the Seventh Day Adventist Church in arranging annual Bible reading activities that are regularly followed by the members of the church and to view the progress reports of the Bible reading activities. Waterfall model has been used as a methodology in this research that is followed by the following steps: (1) Analysis, (2) Design, (3) Implementation, (4) Testing, (5) Maintenance. Through this research, a mobile application was developed and it is used by the Adventist church leaders to create and distribute the daily Bible reading schedules for personal and for families. Through this application also the leaders can receive reports of Bible reading activities progress. In addition, the results of this study facilitate Adventist church members in completing their annual Bible reading activities. This application is still limited to text view and for the future, it is expected to be developed in audio and video formats.